Der Mythos als Ursprache - Tar, Ibolya (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
After discussing some interpretations of myth (Burkert, Jensen, Jaspers, Eliade), the paper deals with the issue of myth’s appearance in literary works. The essential substance of a myth can appear in several treatments, according to the artist’s intention with regard to several interpretations. After a short survey of allegorical interpretations two myths (Orpheus and Eurydice, the golden age) are discussed in their several variations. In connection with the myth of the golden age Vergil’s works are examined to see whether in the Aeneid in particular he created a new myth or rather recreated the myth. In connection with this problem the distinction made between fable and sujet by the Russian formalists is discussed. In answer to the question whether a myth in its artistical appearance can be expressed verbally, Rilke and Hölderlin are cited.